Корпоративна соціальна відповідальність як принцип свідомого капіталізму - Краснокутська, Наталія Станіславівна (НТУ "ХПІ", 2017)
У роботі здійснено порівняння ключових положень концепцій свідомого капіталізму та корпоративної соціальної відповідальності, а також досліджено залежність між впровадженням принципів свідомого капіталізму та позиціями країн в глобальних рейтингах соціально-економічного розвитку. Доведено, що поширення відповідальності бізнесу перед суспільством і довіра у стосунках зі стейкхолдерами має позитивний вплив не тільки на окремі компанії, але і призводить до посилення репутації країн через підвищення їх рангу в глобальних рейтингах.

The article presents comparative analyses of the key concepts of conscious capitalism and corporate social responsibility. It also studies the relationship between the implementation of the principles of conscious capitalism and the country rankings in global ratings and indexes of economic and social development (Country Sustainability Ranking, Global Competitiveness Index, Global Innovation Index, Human Development Index, Ranking of Happiness, Quality of Life Index). The investigation demonstrates that increasing responsibility of business towards society and growing confidence in relationships with stakeholders has a positive impact not only on companies, but also leads to a stronger reputation of countries by raising their ranks in global rankings.
Corporate social responsibility as the principle of conscious capitalism
Keywords: індекси глобальні; розвиток стійкий; розвиток інноваційний; розвиток суспільний; якість життя; global indices; sustainable development; innovative development; society development; quality of life